Evalution of forest fire occurrences in the State of Tocantins - Patriota, Jessica Nepomuceno; Batista, Antonio Carlos; Ganassoli, Eduardo; Santos, Micael Moreira; Coelho, Maria Cristina Bueno; Giongo, Marcos (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
Tocantins is one of the Brazilian states most affected by forest fires, which are the largest remnants of the country's Cerrado. Thus, this study aims to evaluate the Fire Occurrence Records (ROIs) in the state of Tocantins between 2003 and 2015 through the information provided by INPE and SisFogo. The work was divided into three stages: the first consists in the acquisition the images of the satellite AQUA and the fire occurrence records (ROI's), the second comprises the processing of data on satellite images and fire occurrence records through a spreadsheet and the third consists in carrying out the relevant statistics the information collected. The results showed that the amount of heat sources is above the fire occurrence records available through Sisfogo. Of the 139 municipalities in the state, only 14 municipalities were filled with their reports and stored on site. The farms were the sites with higher occurrences of fires in the municipalities and the cause with the highest frequency of fire occurrences were "agricultural activities". The information on hot spots, obtained from satellite imagery, can contribute positively to a better understanding of spatial and temporal dynamics of occurrence of forest fires. In the State of Tocantins, the municipalities: Formoso do Araguaia, Confusion Lagoon, Mateiros and Pium are the ones that presented the highest averages of occurrences of heat sources in the last 12 years. Compared with SisFogo information, these municipalities are also the ones that presented the highest numbers of Fire Occurrence Reports.